Use of Medicinal Plants in Traditional Tibetan Therapy System in Upper Mustang, Nepal - Pandey, Manish Raj (Our Nature, 2007)
The paper deals with 93 species of medicinal plants belonging to74 genera spread over 35 families, which are used in traditional Tibetan therapy system by amchis (medical practitioners) in Upper Mustang. Key words: Amchis, Medicinal plants, Tibetan therapy system, Upper Mustang doi:10.3126/on.v4i1.505 Our Nature Vol. 4(1) 2006 pp69-82